The one percent doctrine deep inside America's pursuit of its enemies since 9/11 - Suskind, Ron (Simon & Schuster Paperbacks, 2007)
What is the guiding principle of the world's most powerful nation as it searches for enemies at home and abroad? Who is actually running U.S. foreign policy? The story begins on September 12, 2001, as America began to gather itself for a response to the unimaginable. Journalist Suskind tells us what actually occurred over the next three years, from the inside out, by tracing the steps of the key actors who oversee the "war on terror" and report progress to an anxious nation; and the invisibles, the men and women just below the line of sight, left to improvise plans to defeat a new kind of enemy in an hour-by-hour race against disaster. The internal battles between these two teams--one, the Bush administration, under the hot lights; the other, actually fighting the fight--reveal everything about what America faces, and what it has done, in this age of terror.--From publisher description.